DIGITAL INNOVATION IN INCLUSIVE DISASTER PREPAREDNESS EDUCATION: DISASTER RISK REDUCTION FOR DEAF STUDENTS THROUGH INTERACTIVE MULTIMEDIA LEARNING - Siska Christianingsih; Abdul Fauzi; Anja Hesnia Kholis; Nurullia Hanum Hilfida; Muhamad Ridlo; La Saudi; Ramdya Akbar Tukan (Universitas Kadiri, 2026)
Children with hearing impairment are part of a vulnerable group that is often overlooked in disaster mitigation programs, largely because of limited access to emergency information and preparedness education. This study aims to evaluate the effectiveness of the Inclusive Disaster Risk Reduction learning intervention (IDRR), delivered through interactive learning media using Articulate Storyline, in improving disaster preparedness knowledge among students who are deaf. A quasi-experimental two-group pre-test and post-test design was conducted, involving 40 students with hearing impairments from special-education senior high schools in Surabaya, Indonesia. The study measured disaster preparedness using a modified preparedness questionnaire adapted from LIPI–UNESCO/ISDR. Paired-sample and independent-sample t-tests were used to analyze the data. The results showed a significant increase in disaster preparedness knowledge in both groups; however, the intervention group exhibited a greater increase (p = 0,02) than the control group (p = 0,04). A significant between-group difference was also observed (mean difference = 5,94; p = 0,008). These findings indicate that IDRR education based on Articulate Storyline is more effective than conventional instruction in improving disaster preparedness knowledge among students with hearing impairments. Interactive multimedia learning is an accessible strategy for strengthening inclusive disaster preparedness education for persons with disabilities in schools.